Stimulus-Organism-Response Theory Model to Understand the Relationship between Customer Experience, Customer Engagement, and Customer Citizenship Behavior, in the Context of Application of 3 Most Popular Fast Fashion in Indonesia - Khairunnisa, Nisrina Najla; Kurniawati, Kurniawati; Siagian, Yolanda Masnita (Ekonomis: Journal of Economics and Business, 2025)
This research aims to analyze consumer behavior in the context of fast fashion and its influence on customer experience. The research method used is qualitative research using a descriptive approach. Data was collected using the Systematic Literature Review model based on the stimulus-organism-response (SOR) theory, this study examines the relationship between customer experience, customer engagement, and customer citizenship behavior in the context of the 3 most famous Fast Fashion in Indonesia. The results show that consumer behavior in the context of fast fashion is influenced by factors such as aesthetics, price, quality, and brand. Customer experience also plays an important role in influencing consumer behavior and their purchasing decisions. Customer Citizenship Behaviour (CCB) also has a role in the context of fast fashion, where consumers' voluntary actions can affect the efficiency of the system and the relationship between companies and consumers. The suggestion for future research is to identify effective strategies to improve customer experience and promote responsible consumer behavior in the context of fast fashion.